PENTINGNYA NILAI AFEKSI DALAM MENINGKATKAN SIKAP RELIGIUS SISWA - Anugerah Helen Suhasri; Fajri Ismail; Win Afgani (CV. ADIBA AISHA AMIRA, 2023)
In the problems that occur at this time, it is found that there is a decline in morals for a student. Moral decline occurs because bad attitudes and behavior are not formed, especially in the school environment. One of the factors is the lack of hiding the value of affection for students. Affective or affective is one of the three domains that are targeted in the learning process. Affective has been a part of learning in schools for decades. It appears in many different forms such as humanist education, moral development, self-actualization, value education and others. Affect also appears as a response to various social needs, such as the widespread use of illegal drugs and promiscuity. At the age of elementary school to early middle school, generally forms of behavior that often occur in the school environment, one of which is dishonesty. The nature of honesty which is very important in life turns out to be very difficult for students to apply. this is because there is no emphasis on moral education that is based on the Al-Qur'an and As-Sunnah. The moral education in question is the values ​​of affection which become the realm in the promotion process of the affective assessment. To instill the value of affection, as an educator who plays a very important role in providing moral education, remembering that this value of affection is very important in forming good attitudes according to Islamic religious guidance.